2013
DOI: 10.2474/trol.8.1
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Investigation of Oil Film Temperatures in Elliptical Profile Journal Bearing

Abstract: Hydrodynamic journal bearings experience significant variation in oil film temperature. Reliable data of operating temperatures in these journal bearings are very useful and important for practical bearing designers and mathematical modellers. Here, an elliptical journal bearing has been tested to access the temperature rise at oil-bush interface with three grade oils at loads varying from 100 N to 600 N and speeds = 3000, 3500, 4000 rpm at constant oil supply pressure. The results show that with increase in l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Figure 1 shows a schematic form of elliptical bearing. The non-dimensional film thickness is given as 12 where …”
Section: Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 1 shows a schematic form of elliptical bearing. The non-dimensional film thickness is given as 12 where …”
Section: Modelingmentioning
confidence: 99%
“…empirically analyzed oil temperature in elliptical bearing. 12 Singla et al. empirically examined temperature and pressure profile in an elliptical bearing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ostayen and Beek [15] have presented a thermo-hydrodynamic model for analyzing a lemon-bore journal bearing through finite element method and the presented model is used to check the design of the lemon bore bearings in a specific naval application. Chauhan et al [16][17] and Sehgal et al [18][19] evaluated thermal performance parameters theoretically and experimentally for offset and elliptical bearing (also named as two lobes) considering three different grades of oils. The authors have also evaluated the temperature of oil film along the circumference of the bearing at various speeds and loads.…”
Section: Introductionmentioning
confidence: 99%
“…Rakesh Sehgal 13 conducted an experimental investigation on phosphorous bronze noncircular journal bearings using different lubricants at constant load and reported that maximum temperature is obtained in the case of Hydrol in comparison with 2T and multigrade oils. Rakesh Sehgal et al 14 conducted an experimental investigation on elliptical profile hydrodynamic journal bearings to study the dynamic characteristics and reported that with an increase in the radial load, the temperature and pressure also increased along the midplane of the lobe. Rakesh Sehgal et al 15 conducted an experimental analysis to compare the bearing performance characteristics of circular bearings and reported that offset bearings can withstand higher temperatures than cylindrical bearings.…”
Section: Introductionmentioning
confidence: 99%